(untitled) - Nixon, Mark S. (Amsterdam, 2008)
This is book introduction about amages, sampling and frequency domain processing, basic image processing operations, low-level feature extraction, feature extraction by shape matching...
Keywords: Image processing,Xử lý ảnh